Patterns of 137Cs accumulation in herbaceous plant communities near the Chernobyl Nuclear Power Plant in the aftermath of the accident - Nikitin, Aleksander; Shurankova, Olga; Kalinichenko, Sergey; Mishchanka, Egor; Leferd, Galina (Journal of the Belarusian State University. Ecology, 2024)
Radioactive cesium isotopes often significantly determine the severity of nuclear accidents with the release of radioactive substances into the environment. Therefore, identifying the patterns of their behavior in various ecosystems, their transfer in food chains, and design effective methods for regulation of these processes are of current interest. The aim of this work was to find the patterns of 137Cs accumulation by herbaceous plants in natural ecosystems at the stage of the remote consequences of the Chernobyl NPP disaster. Three experimental sites were selected at a distance of 13–16 km from the accident epicenter. At each site, sample plots were established to study the characteristics of the vegetation cover and soil. To confirm the impact of the moisture regime on the accumulation of 137Cs by plants, a vegetation experiment was also conducted. The analysis did not reveal a direct link between the gross soil contamination indicators with 137Cs, its soluble, ion-exchange, and labile forms in the soil with the accumulation of the radionuclide by the above-ground parts of Elytrigia repens (L.) Nevski, Calamagrostis epigejos (L.) Roth, Poa pratensis L. and Carex brizoides L. Among the complex of edaphic factors, the closest relationship with the specific activity of 137Cs in the aboveground parts of cereal plants is associated with the volumetric water content in the soil, the content of mobile K2O, and the labile form of the radionuclide extractable with tetraphenylborate. The inverse exponential character of the relationship between these parameters and the accumulation of 137Cs is mediated by K-dependent mechanisms of Cs absorption and a decrease in the effective diffusion of K from the soil solution to the root surface as soil moisture decreases. For the sedge, the K-dependent mechanism of regulating the root absorption of Cs was not confirmed. An experiment under controlled conditions confirmed a significant increase in the accumulation of 137Cs by grass plants with a decrease in moisture availability, caused by the activation of K transporters with high affinity for both this element and Cs.